2000
DOI: 10.1038/sj.cr.7290043
|View full text |Cite
|
Sign up to set email alerts
|

Activation of phospholipase D activity in transforming growth factor-beta-induced cell growth inhibition

Abstract: The data presented suggest that PLD activation is involved in the TGF-β 1 -induced cell growth inhibition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…Interestingly, TGFβ1 could induce the expression of arachidonic acid synthase PLA2G4A and PLCG2 , although arachidonic acid could not induce the expression of TGFβ1 in Eph4 cells. The similar phenomenon was also observed in other cell lines [36, 37]. TGFβ1 activates the PLA2 in cultured rat costochondral chondrocytes [36].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Interestingly, TGFβ1 could induce the expression of arachidonic acid synthase PLA2G4A and PLCG2 , although arachidonic acid could not induce the expression of TGFβ1 in Eph4 cells. The similar phenomenon was also observed in other cell lines [36, 37]. TGFβ1 activates the PLA2 in cultured rat costochondral chondrocytes [36].…”
Section: Discussionsupporting
confidence: 82%
“…TGFβ1 activates the PLA2 in cultured rat costochondral chondrocytes [36]. TGFβ1 also activates phospholipase D activity and increases the production of arachidonic acid precursor, diacyl-glycerol (DAG), in lung and kidney epithelial cells [37]. Those results indicate that TGFβ1 signalling pathway may stimulate the arachidonic acid synthesis during the involution period.…”
Section: Discussionmentioning
confidence: 99%
“…Investigating the signaling pathways induced by TGF-β is important for the understanding of the mechanism that underlies the various biological events mediated by TGF-β. It was demonstrated that increased PLD activity are involved in TGF-β-induced growth inhibition of several types of epithelial cell lines [3]. TGF-β can induce apoptosis in normal hepatocytes [4][5][6][7] and hepatoma cells [8], [9].…”
Section: Introductionmentioning
confidence: 99%
“…Aberrant PLD activity has been identified in chronic inflammatory autoimmune disorders and in allergic asthma (Choi et al., 2015, Kang et al., 2013). Moreover, TGF-β1 increases PLD activity and increases the levels of PA and PA-related metabolites in epithelial cell lines (Zhou et al., 2000). We sought to establish whether there is a link between PLD and the TGF-β1 suppression of GC activity.…”
Section: Discussionmentioning
confidence: 99%